Transferrin Receptor-Targeted Nanocarriers: Overcoming Barriers to Treat Glioblastoma - Maria João Ramalho; Joana Angélica Loureiro; Manuel A. N. Coelho; Maria Carmo Pereira (MDPI AG, 2022)
Glioblastoma multiforme (GBM) is the most common and lethal type of brain tumor, and the clinically available approaches for its treatment are not curative. Despite the intensive research, biological barriers such as the blood-brain barrier (BBB) and tumor cell membranes are major obstacles to developing novel effective therapies. Nanoparticles (NPs) have been explored as drug delivery systems (DDS) to improve GBM therapeutic strategies. NPs can circumvent many of the biological barriers posed by this devastating disease, enhancing drug accumulation in the target site. This can be achieved by employing strategies to target the transferrin receptor (TfR), which is heavily distributed in BBB and GBM cells. These targeting strategies comprise the modification of NPs' surface with various molecules, such as transferrin (Tf), antibodies, and targeting peptides. This review provides an overview and discussion on the recent advances concerning the strategies to target the TfR in the treatment of GBM, as their benefits and limitations.